Can healthcare apps and smart speakers improve the health behavior and depression of older adults? A quasi-experimental study - Kim, Dasom (Frontiers in Digital Health, 2023)
Purpose: This study aimed to identify the effects of health management information and communication technologies (ICT) on adults aged 65 years or older. Methods: Older adults registered at public health centers were provided with a health management app and a smart speaker for six months, and health missions were provided to them. Depression, exercise self-efficacy, number of days of moderate-intensity exercise, relative grip strength, balance test, and five time-sit-to-stand tests were measured as the same items during the pre- and post-evaluation. The degree of change between the group using only the health management app and the group using the smart speaker and the health management app was compared to analyze whether there were additional health benefits for the smart speaker. Results: It was found that both groups showed a positive health status and behavioral changes post-evaluation. However, in the group that was additionally provided with smart speakers, there was no reduction in depression due to the communication and music-listening functions. Conclusion: This study concluded that healthcare using ICT can be sufficiently attempted even for older adults. However, to provide an ICT device for health management of the socially and economically vulnerable older adults in the public domain, it should be introduced after verifying whether it meets the purpose and goal expected by the national health project.